Literasi Digital dan Kinerja UMKM: Peran Mediasi Inovasi Produk dan Akses Permodalan di Kabupaten Minahasa - Purba, Pebisitona Mesajaya; Cristofer Sumiok; Andrew P. Marunduh (Universitas Methodist Indonesia, 2026)
This study aims to analyze the effect of digital literacy on MSME performance with product innovation and access to capital as mediating variables among MSMEs in Minahasa Regency, North Sulawesi Province. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. The population consists of MSMEs registered with the Department of Cooperatives and SMEs of Minahasa Regency, with a total of three thousand eight hundred and seventy-four business units based on official data from the Department of Cooperatives and SMEs of North Sulawesi Province (Diskopukm Sulutprov, 2022). A final sample 53 respondents was selected through purposive sampling with strict inclusion criteria. The results show that digital literacy has a significant positive direct effect on product innovation, access to capital, and MSME performance. Product innovation and access to capital also significantly influence MSME performance. Mediation testing confirms that both product innovation and access to capital partially mediate the relationship between digital literacy and MSME performance, with product innovation serving as the more dominant mediating pathway. The coefficient of determination for MSME performance is high, indicating that the research model has strong explanatory power. These findings underscore the strategic importance of strengthening digital literacy as a key lever for enhancing MSME competitiveness in regional economic contexts.